Physical testing on formulated earthworm-based pellets for growth performance evaluation in African catfish (Clarias gariepinus) - Kulaab Liam (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
Pellets potential was evaluated by determining the growth performance of African catfish (Clarias gariepinus) fed with heated earthworm-based fish pellets. Fish experimental was conducted for 8 weeks by comparing weekly weight of the fish fed with heated earthworm-based pellets and commercial pellets. The growth performance of heated earthworm-based pellets showed higher weight and length increment compared to existing commercial pellets.